Laying open and curettage – optimal method for pilonidal sinus treatment: review of the literature - Makūnaitė, Gabija; Danys, Donatas; Strupas, Kęstutis; Poškus, Tomas (Lietuvos chirurgija, 2017)
ObjectiveThe aim of the article is to review the literature concerning pilonidal sinus treatment and to suggest the optimal method.MethodsUsing PubMed electronic database the literature published in the period 2010–2016 on pilonidal sinus treatment was reviewed. The keywords of the search were: pilonidal sinus, curettage, excision, drenage, recurrence. The articles, presenting data on basis of randomized controlled trials and including more than 1000 patients, were analized. To review the long- term results after treatment, the data of prospective randomized studies was analized.ResultsStudies, presenting the effectiveness of the different treatment methods of pilonidal sinus were included in this analysis. The outcome parameters were operating time, healing time, recurrence, complication rate and return to work time. 13 studies were included for the analysis to compare the results of different surgical techniques: the systematic review of the studies done for laying open plus curettage (LOC) procedure reported the recurrence rate – 4.47%, whereas in excision with open healing, it is 11.9%, in excision with marsupialization to 7.1%, in excision with midline closure 20%, and in excision with off midline closure 11%. The mean operating time in LOC is 34.6 min, which is shorter than in other techniques (reaches 89 min). The complication rate in LOC (1.44%) is also lower (as compared to excision with open healing 23.8%). The median time to return to work in LOC is 8.4 days, whereas in different methods it reaches 43 days. The median days taken in wound healing in LOC also seem shorter. In seven out of 13 studies, this procedure was feasible under local anaesthesia. The similar conclusion was drawn by all the studies performing this procedure.ConclusionsEvidence suggests that some of the questions of which is the best surgical technique for pilonidal sinus have now been answered – a “less is more” approach is warranted. Laying open of the pilonidal sinus with curettage of the cavity should be the first-line procedure for pilonidal sinus disease. It has distinct advantages – low recurrence and complication rate, easy to reproduce, short operating time, low cost, possible to do this operation under local anaesthesia, less pain and early return to work time.
Keywords: pilonidal sinus; curettage; excision; drenage; recurrence